Ice Jams in New Hampshire. Ice Engineering. Number 26, October 2000 - Herrin, Lourie; White, Kate; Eames, Heidi (2000)
An ice jam is an accumulation of ice in a river that restricts water flow and may cause backwater that floods low-lying areas upstream from the jam. Areas below the ice jam can also be affected when the jam releases, sending water and ice downstream. Damages resulting from ice jams can affect homes, buildings, roads, and riverine structures; block hydropower and water supply intakes; and decrease downstream discharge. Roads may be flooded and closed, or bridges weakened or destroyed, limiting emergency and medical relief to the affected areas. The potential exists for death or serious injury due to jam and flood conditions, as well as during evacuations and other ice mitigation operations. Ice movement and ice jams also can severely erode streambeds and banks, with adverse impacts on fish and wildlife habitat. The original document contains color images.